Current and Potential Therapies Targeting Inflammation in NASH - Albhaisi, Somaya; Noureddin, Mazen (Frontiers in Endocrinology, 2021)
Nonalcoholic steatohepatitis (NASH) is the progressive form of nonalcoholic fatty liver disease (NAFLD) and is characterized by hepatic steatosis, inflammation, hepatocellular injury and fibrosis. Inflammation plays a key role in promoting the progression of NASH and can be provoked by intrahepatic (e.g., lipotoxicity, immune responses, oxidative stress and cell death) and extrahepatic sources (adipose tissue or gut). The identification of triggers of inflammation is a central issue in understanding the mechanisms implicated in NASH development and progression and designing targeted therapies able to halt or reverse disease progression. In this review, we summarize the current and potential therapies targeting inflammation in NASH.